Dietary Linalool is Transferred into the Milk of Nursing Mothers - Debong, Marcel; N'Diaye, Katharina; Owsienko, Diana; Schoberl, Daniela; Ammar, Tayyaba; Lang, Roman; Büttner, Andrea; Hofmann, Thomas; Loos, Helene (Molecular Nutrition & Food Research, 2021)
Scope: Breast milk is repeatedly postulated to shape the first aroma and taste impressions of infants and thus impact their flavor learning. The objective of this study is to assess the transition of aroma compounds from a customary curry dish into milk. Methods and Results: The article prepares a standardized curry dish and administers the dish to nursing mothers (n = 18) in an intervention study. The participants donate one milk sample before and three samples after the intervention. Due to their olfactory or quantitative relevance in the curry dish, 1,8-cineole, linalool, cuminaldehyde, cinnamaldehyde, 4-hydroxy-2,5-dimethyl-3(2H)-furanone, sotolone, eugenol, vanillin, and γ-nonalactone are defined as target compounds, and their transition into milk is quantified by gas chromatography-mass spectrometry. A significant transition into the milk is observed for linalool, and its olfactory relevance in this respect is supported by calculated odor activity values. In contrast, no relevant levels are detected for the other eight target compounds. Conclusion: Ingestion of a customary curry dish can lead to an alteration of the milk aroma, which might be perceived by the infant during breastfeeding. The current study also demonstrates that the extent of aroma transfer differs between both substances and individuals.
Created from Fastlane, Scopus look-up
Keywords: aroma transition; breast milk; flavor learning; linalool; maternal diet

Identification and Quantification of Volatile Ramson-Derived Metabolites in Humans - Scheffler, Laura; Sharapa, Constanze; Ammar, Tayyaba; Büttner, Andrea (Frontiers in Chemistry, 2018)
Ramson (Allium ursinum) is known for its typical garlic-like aroma. Both ramson and garlic belong to the genus allium which is characterized by a high content of sulfurous compounds. However, in contrast to garlic, ramson is in general not associated with an unpleasant breath following consumption. While there is data available regarding the metabolism of volatile garlic constituents in the human body, the metabolism of ramson was not yet addressed. To elucidate if ramson has an impact on the body odor, this study aimed at identifying volatile ramson-derived metabolites in human milk and urine. Therefore, milk and urine samples were gathered before and after ramson consumption, and were analyzed sensorially by a trained human sensory panel as well as chemo-analytically applying gas chromatography-mass spectrometry/olfactometry (GC-MS/O). Sensory evaluation revealed a garlic-/cabbage like odor in milk samples obtained after ramson consumption, demonstrating that ramson consumption affected the milk aroma. Analyzes by means of GC-MS/O further confirmed excretion of three ramson-derived metabolites in milk and urine samples collected after ramson consumption, namely allyl methyl sulfide (AMS), allyl methyl sulfoxide (AMSO) and allyl methyl sulfone (AMSO(2)). Of these metabolites only AMS had a garlic-/cabbage-like odor, while the other two were odorless. These metabolites were subsequently quantified using stable isotope dilution assays. Nine urine sets, each comprising eight urine samples, and nine milk sets, each comprising four samples, were analyzed. In case of the urine sets a time interval of about 24 h was monitored, in case of the milk sets a time interval of up to 9 h. Despite the fact that all samples contained the same metabolites there were relevant differences found between individual subjects, especially with regard to the temporal rate of metabolite excretion. Generally, the maxima of metabolite excretion were observed in milk sets within 3 h after ramson consumption. In urine the highest AMS and AMSO amounts were observed within 2 h whereas the maximum concentration of AMSO(2) was reached about 2 to 4 h after ramson ingestion. This study suggests that ramson constituents are heavily metabolized in the human body.
Keywords: human milk; human urine; gas chromatography mass-spectrometry/olfactometry; allyl methyl sulfide; allyl methyl sulfoxide; allyl methyl sulfone; stable isotope dilution analysis (SIDA)